Epidemiological, Pathophysiological, and Clinical Considerations on the Interplay between Thyroid Disorders and Type 2 Diabetes Mellitus - Gregory Grigoriadis; Theocharis Koufakis; Kalliopi Kotsa (Medicina, 2023)
Thyroid disorders (TD) and diabetes mellitus (DM) are the two endocrinopathies with the highest prevalence in the general population that frequently coexist. Thyroid dysfunction is more common in people with type 2 diabetes mellitus (T2DM) compared to normoglycemic individuals. Untreated TD can impair glycemic control, increasing the risk of diabetes complications. Hyperinsulinemia can affect the morphology of the thyroid gland by promoting the proliferation of thyroid tissue and increasing the size of thyroid nodules. Metformin can confer benefits in both endocrinopathies, while other antidiabetics, such as sulfonylureas, can negatively affect thyroid function. Animal and human observational data suggest an increased risk of medullary thyroid carcinoma after treatment with glucagon-like peptide-1 receptor agonists. However, randomized trials have so far been reassuring. Furthermore, some observational studies suggest an association between thyroid cancer and T2DM, especially in women. This narrative review aims to shed light on the epidemiological, pathophysiological, and clinical aspects of the interplay between TD and T2DM. Taking into account the important clinical implications of the coexistence of T2DM and TD, proper screening and management strategies are needed for both endocrinopathies to ensure optimal patient care.